2017
DOI: 10.1021/acs.macromol.7b00197
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Ion Conduction Mechanism in Imidazolium-Based Poly(ionic liquids): A Comprehensive Investigation of the Structure-to-Transport Interplay

Abstract: Polymerized ionic liquids (poly­(ILs)) are considered highly promising for the realization of high-performance and intrinsically safer electrolytes for rechargeable batteries due to their high charge density. However, to date little is known about the ion conduction mechanism for this class of solid polymer electrolytes (SPEs). Herein, we performed an in-depth characterization of a homologous series of 1-alkyl-3-vinylimidazolium bis­(trifluoro­methane)­sulfonimide-derived homopolymers, i.e., p­(C n VIm-TSI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 69 publications
4
65
6
Order By: Relevance
“…6). Following the earlier work on rigid polymers [73][74][75][76][77] as well as rather recent studies, 88,89 Delhorbe et al 87 assigned this finding to the frustration in polymer packing related to the bulky imidazolium cation being is closely bonded to the polymer backbone, which result in sufficient free volume for the anions to move. Moreover, they reported additional studies for such poly(IL)s including LiTFSI, showing that the addition of the lithium salt may not lead to substantial changes in the ion conduction mechanism.…”
Section: B) Frustrated Polymers and Polymerized Ionic Liquidsmentioning
confidence: 85%
See 2 more Smart Citations
“…6). Following the earlier work on rigid polymers [73][74][75][76][77] as well as rather recent studies, 88,89 Delhorbe et al 87 assigned this finding to the frustration in polymer packing related to the bulky imidazolium cation being is closely bonded to the polymer backbone, which result in sufficient free volume for the anions to move. Moreover, they reported additional studies for such poly(IL)s including LiTFSI, showing that the addition of the lithium salt may not lead to substantial changes in the ion conduction mechanism.…”
Section: B) Frustrated Polymers and Polymerized Ionic Liquidsmentioning
confidence: 85%
“…While Winey and co-workers 86 suggested that this energy barrier increases with an increasing alkyl chain length, Delhorbe et al 87 investigated an extended set of C n VImTFSI poly(IL)s with n = 2, 4, 6, 8, and 10, showing that such "linear" conclusions have to be taken with care. According to their results, the ion conduction in such systems is governed by a rather complex interplay of physicochemical properties (including the T g ), the charge carrier concentration, and the eventual formation of nanostructures.…”
Section: B) Frustrated Polymers and Polymerized Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) for a similar imidazolium-based polyIL. 27,28 Together, such observations have raised the question, 29 "what are the mechanisms underlying the influence of the linker side-chain length on the transport properties of polyILs? "…”
mentioning
confidence: 99%
“…While mostly imagined as solvents and/or electrolytes, [17,18] their use as a monomer is more recent. A variety of polyelectrolytes or "poly-ionic liquids" (PILs) have been synthesized from IL precursors and used as ion conductors, [19][20][21][22] binders, [23][24][25][26] metal stabilizers, [27,28] among others. [29] Their preparation is typical of other free-radical polymerizations and can be controlled to create block-copolymers, [30,31] dendrimers/branched poly-mers, [32,33] and others.…”
Section: Introductionmentioning
confidence: 99%